14C data and the early colonization of Northwest South America: A critical assessment - Delgado Burbano, Miguel Eduardo (2015)
The aim of this paper is to make a critical appraisal of the available 14C dataset from Northwest South America (Colombia) corresponding to the Pleistocene/Holocene transition (ca. 12,000-8000 14C years BP). The first step in the study was to assemble from both published and unpublished sources an exhaustive database of 14C dates (n=85), recording data regarding the environmental setting and spatial coordinates of each site, stratigraphic provenance of the dated samples, material used for dating, and 14C dating method. After the application of different filtering procedures based on outlier detection techniques, the database was subsequently reduced (n=77). Using uncalibrated and calibrated dates, some spatial and temporal trends in data distribution were investigated in order to illustrate both the strengths and weaknesses of the available database. It is concluded that three main features that characterize the 14C dataset from Northwest South America, namely the very high percentage of 14C measurements made on charcoal, the almost total disregard of bone as a target sample for dating, and the extremely low percentage of AMS dates, partially affect both its reliability and comparability. It is suggested that, in order to use 14C dates as data to make reliable inferences about the timing, pattern, process and tempo of early exploration and colonization of the study area, work at two different levels would be profitably carried out. In the short term, it would be advisable to develop an extensive and exhaustive program aimed at redating, with AMS and new sample selection criteria, the more significant archaeological assemblages attributable to the Pleistocene/Holocene transition. In the medium to long term, it would be necessary to implement new research projects specifically aimed at obtaining original information about early human settlement in different geographical areas of the Colombian territory.